2014
DOI: 10.1371/journal.pone.0105550
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Promotes K-Ras-Induced Lung Tumorigenesis through BASCs Amplification

Abstract: Oncogenic K-Ras represents the most common molecular change in human lung adenocarcinomas, the major histologic subtype of non–small cell lung cancer (NSCLC). The presence of K-Ras mutation is associated with a poor prognosis, but no effective treatment strategies are available for K-Ras -mutant NSCLC. Epidemiological studies report higher lung cancer mortality rates in patients with type 2 diabetes. Here, we use a mouse model of K-Ras-mediated lung cancer on a background of chronic hyperglycemia to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Another study has reported the translocation of GLUT1 and GLUT4 on the cell surface by insulin treatmen via a different pathway of signal transduction in mouse NIH3T3-L1 adipocytes [ 38 ]. In addition, a previous study has reported that the chronic hyperglycemia also upregulated GLUT1 expression and promoted the K-Ras-induced lung tumorigenesis in mice [ 39 ]. In the present study, the Western blot analysis did not demonstrate positive GLUT4 expression in KD cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has reported the translocation of GLUT1 and GLUT4 on the cell surface by insulin treatmen via a different pathway of signal transduction in mouse NIH3T3-L1 adipocytes [ 38 ]. In addition, a previous study has reported that the chronic hyperglycemia also upregulated GLUT1 expression and promoted the K-Ras-induced lung tumorigenesis in mice [ 39 ]. In the present study, the Western blot analysis did not demonstrate positive GLUT4 expression in KD cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, there is a positive correlation between GLUT1 expression and the EGFR and KRAS oncogenes; GLUT1 overexpression is also correlated with an aggressive phenotype [127]. In an in vivo study by Micucci et al, the hyperglycemic state induced by streptozotocin accelerated lung cancer progression [128]. Hyperglycemia induces reactive oxygen species (ROS) production by increasing oxidative stress, decreases mitochondrial function and tilts the metabolic processes to glycolysis [120,129].…”
Section: Metabolic Adaptations Induced By Hypoxia In Cancermentioning
confidence: 99%
“…Moreover, our current study provides compelling evidence that hyperglycemia, after activation of oncogenic K-Ras, exerts its pro-tumorigenic effects by maintaining a sub-population of cancer tumor-initiating cells, namely lung bronchio-alveolar stem cells (BASCs) [56]. …”
Section: Mechanisms That Increase the Risk Of Cancer In Metabolic Synmentioning
confidence: 99%